Cyanosis as Mortality Risk among Children with Severe Pneumonia - Fadlinda, Herza; Utomo, Adi; Djuhaeni, Henni (Althea Medical Journal, 2016)
Background: Pneumonia is the second leading cause of infant death in Indonesia. The mortality ofÂ pneumonia in children is associated with cyanosis, malnutrition, and age less than 4 months. The aim of thisÂ study was to determine the relationship between cyanosis, malnutrition, and age less than 4 months withÂ the mortality of infant patients with severe pneumonia at Dr Hasan Sadikin General hospital.Methods: A case-control study has been conducted using medical records of 80 patients with pneumoniaÂ at Dr. Hasan Sadikin General Hospital, period January 2007 to December 2013. The inclusion criteriaÂ were medical records consisting of information about infants with severe pneumonia, without comorbidÂ diagnoses, who died during hospitalization. While controls were infants who have been discharged fromÂ hospital. The independent variables of this study were cyanosis, malnutrition, and age less than 4 months,Â while the dependent variable was the mortality. Data were analyzed by using univariate and bivariateÂ analysis.Results: The study reported that only cyanosis was associated with mortality. Malnutrition and age lessÂ than 4 months were not associated with mortality.Conclusions: Cyanosis is known to be the only factor that has affected the mortality of infants withÂ pneumonia who are hospitalized at Dr. Hasan Sadikin General Hospital. [AMJ.2016;3(2):186â9]DOI:Â 10.15850/amj.v3n2.799